Foreign Bank Presence and Its Effect on Firm Entry and Exit in Transition Economies - Olena Havrylchyk (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This study investigates the impact of foreign bank penetration in Central and Eastern Europe on firm entry. We demonstrate that the acquisition of domestic banks by foreign investors has led to reduced firm creation, smaller average size of entrants and increased firm exit in opaque industries compared to transparent ones. At the same time, the entry of greenfield foreign banks spurred firm creation and exit. Unlike previous studies, which use interchangeably the notions of opacity and size, we define opacity in terms of technological process and show that economic significance of foreign bank entry is larger for opaque industries than for industries with large shares of small firms. Our findings can be interpreted as evidence of increased credit constraints and are consistent with theories that argue that foreign bank presence exacerbates informational asymmetries.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: E51; G21; M13; 330; Entrepreneurship; Foreign bank entry; Asymmetric information; Credit constraints